Administration of Islamic law and human rights: The basis and its trajectory in Malaysia - Shuaib, Farid Sufian (2017)
This paper looks at the interplay between the administration of Islamic law in Malaysia in relation to Islamic family law and Islamic criminal law and human rights. The paper examines the basis of the administration of Islam in Malaysia relating to its history and post-independence mandate. It looks at the position of human rights under the Federal Constitution and the position of the administration of Islamic law under the constitutional framework. The research found that entrenching of the fundamental liberties through the supremacy clause resulted in the prevalence of human rights over freedom of religion. However, this is not consistently arrived at since the constitutional frameworks allows for plurality of laws and exclusion of personal law from the principle of equality.